Pazopanib with 5‐FU and oxaliplatin as first line therapy in advanced gastric cancer: A randomized phase‐II study—The PaFLO trial. A study of the Arbeitsgemeinschaft Internistische Onkologie AIO‐STO‐0510. Issue 6 (15th November 2021) - Högner, Anica; Al‐Batran, Salah‐Eddin; Siveke, Jens T.; Lorenz, Mario; Bartels, Prisca; Breithaupt, Kirstin; Malfertheiner, Peter; Homann, Nils; Stein, Alexander; Gläser, Dietrich; Tamm, Ingo; Hinke, Axel; et al.
Abstract: VEGF inhibition in gastric cancer has a proven benefit in the second line setting. Pazopanib, an oral tyrosine kinase inhibitor, selectively inhibits VEGFR‐1, ‐2 and ‐3, c‐kit and PDGF‐R resulting in inhibition of angiogenesis. This open‐label randomized phase II trial (2:1) investigated the efficacy of combining pazopanib with FLO (5‐fluorouracil, oxaliplatin) vs FLO alone (internal control arm) as first‐line treatment in patients with advanced adenocarcinoma of the stomach and gastroesophageal junction (GEJ). Eighty‐seven patients were randomized and 78 patients were eligible and evaluable (PaFLO arm 51 patients, FLO arm 27 patients). The PFS rate at 6 months (primary endpoint) was 34% in the PaFLO arm vs 30% in the FLO arm. Comparing PaFLO with FLO median PFS was 4.66 months (95% confidence interval [CI] 2.87‐6.46) vs 4.47 months (95% CI 1.79‐7.14) (95% CI, hazard ratio [HR] 0.96 (0.60‐1.55), P = .882 [exploratory]); median OS was 10.19 months (95% CI 5.46‐14.92) vs 7.33 months (95% CI 4.93‐9.73), (95% CI HR 1.01 [0.62‐1.65], P = .953, exploratory), disease control rate was 72% vs 59%. PaFLO was well tolerable, toxicities were slightly higher in the PaFLO arm. Major adverse events were loss of appetite, nausea, fatigue, diarrhea, neutropenia and thrombocytopenia. Adding pazopanib to chemotherapy shows signs of efficacy but no major improvement in this randomized phase 2 trial. The PFS at 6 months in both arms was lower than expected from the literature. Biomarkers identifying subgroups who benefit and novel combinations are needed. ClinicalTrials.gov : NCT01503372. Abstract : What's new? Pazopanib is an oral angiogenesis inhibitor. In this randomized, phase II clinical trial, the authors added pazopanib to standard chemotherapy as a first‐line treatment in patients with advanced gastro‐esophageal cancer. This combination was compared to chemotherapy alone. The results indicated that the addition of pazopanib to 5‐FU/oxaliplatin was well tolerated and showed some efficacy, but didn't yield a major benefit over standard therapy. Further research into other novel treatment combinations, as well as into biomarkers to identify subgroups who might benefit, are urgently needed.